THE IMPLEMENTATION OF DIABETIC SELF-MANAGEMENT IN INDONESIA AND TAIWAN HOSPITAL: A CASE STUDY DESIGN - Satriya Pranata; Hei-Fen Hwang (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Population of people with diabetes mellitus (DM) are increasing every year. As a chronic illness, patients with DM needs to practice self-management for life. Adopted the nursing system in other countries that are more advanced in DM care, however the study is still under investigation. Objectives: primary objective was to analyze the diabetic Self-management among the Indonesian and Taiwan population in Hospital. Secondary was to develop theory-guided and/or evidence-based nursing model in the self-management among diabetic patient with practical issues. Methods: We used a case study design by discussion across the multi-discipline of health care provider point of view, observation and brief interview session with patient, observe the health care model, learning process of health education between nurse and patient and whole application of the health education, at Veteran Hospital in Taiwan and Manambai Abdulkadir Hospitals in Indonesia. Results: Education system related to self-management of DM patients have been running and prepared by the Veteran hospital in Taiwan. The health system for diabetes management was called by diabetes shared care. Nurse, nutritionist and doctor have similar opinions about self-management in DM patients in Taiwan but different perspective among health professionals in Indonesia. The process of applying of evidence-based nursing practice and guidelines for providing health education to patients in Veteran Hospital Taiwan was using guidelines from the diabetes federation of China (Taiwan), on the other hand, standard operating procedure in Hospital in Manambai Abdulkadir Hospital, Indonesia, it is due to different policy in each country. Conclusion: The model of self-management might can be successfully be applied in clinical setting with several strategies by resolve the challenges. Hopefully, this study can be providing valuable information to the health professionals in order to provide the best service for patients with DM.